1997
DOI: 10.1039/a606715h
|View full text |Cite
|
Sign up to set email alerts
|

Selective dimerization by a radical chain reaction in γ-irradiated crystals of 1,3-bis(3-acetoxyprop-1-ynyl)-4-methoxy-6-methylbenzene

Abstract: A single dimer is formed by a radical chain reaction upon γ-irradiation of 1,3-bis(3-acetoxyprop-1-ynyl)-4-methoxy-6-methylbenzene (1) crystals, sealed in a glass ampoule under vacuum at room temperature. The dimerization is initiated by the addition of the prop-2-ynyl-type radical attached at the 1-position of the benzene ring to the β-carbon of the triple bond attached at the 3-position of the benzene ring. The resulting vinyl radical undergoes H-abstraction from the prop-2-ynyl methylene of the 3-acetoxypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The formation of both carbon–carbon bonds and hydrogen atom transfer is unequivocally topochemical, stereospecific, and not the result of a random process . , As indicated above, γ-ray-initiated solid-state polymerization reactions have been extensively studied. On the other hand, there are very few examples of reactions of radical chain solid-state reactions that lead cleanly to monomeric, dimeric, or trimeric compounds. In addition to the formation of 3 , 5 , 7 , 9 , and 11 , the only examples we are aware of are the isomerizations of α-lactose monohydrate, , D-fructose, , and 2-deoxy-β-D- erythro -pentoypyranose , and the dimerization of a bis alkyne . In all of the highly stereospecific reactions we studied, the single crystals become amorphous as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of both carbon–carbon bonds and hydrogen atom transfer is unequivocally topochemical, stereospecific, and not the result of a random process . , As indicated above, γ-ray-initiated solid-state polymerization reactions have been extensively studied. On the other hand, there are very few examples of reactions of radical chain solid-state reactions that lead cleanly to monomeric, dimeric, or trimeric compounds. In addition to the formation of 3 , 5 , 7 , 9 , and 11 , the only examples we are aware of are the isomerizations of α-lactose monohydrate, , D-fructose, , and 2-deoxy-β-D- erythro -pentoypyranose , and the dimerization of a bis alkyne . In all of the highly stereospecific reactions we studied, the single crystals become amorphous as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of triaquabis(trans-2-butenoato)magnesium (6) nose 36,41 and the dimerization of a bis alkyne. 42 In all of the highly stereospecific reactions we studied, the single crystals become amorphous as the reaction proceeds. While there are many examples of single-crystal-to-single-crystal transformations that arise from thermal and/or photochemical processes, 43,44 we are unaware of examples of γ-ray-induced transformations that proceed to monomeric, dimeric, or trimeric compounds with retention of single-crystal quality.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on the reactions of γ-irradiated crystals of diethynylbenzene derivatives. [1][2][3] The crystal structures of the monomers were markedly affected by the nature of the substituents and their positions in the aromatic ring, leading to a variety of solid-state reactivities. Polymerization or dimerization occurred selectively depending on the crystal structures in contrast to the non-selective reactivities in solution.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is concerned with the crystal structures and solid-state polymerization of bifunctional derivatives having diacetylene moieties. The structures and the melting points of the monomers, 1,4-bis(5-hydroxypenta-1,3-diynyl)benzene (1), 1,2-bis(5-hydroxypenta-1,3-diynyl)benzene (2) and 1-(5-hydroxypenta-1,3-diynyl)-4-ethynylbenzene (3), used in the present study, are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%